Exploring the boundary of a specialist service for adults with intellectual disabilities using a Delphi study: a quantification of stakeholder participation. (22nd July 2013) - Hempe, Eva‐Maria; Morrison, Cecily; Holland, Anthony
Abstract: Background: There are arguments that a specialist service for adults with intellectual disabilities is needed to address the health inequalities that this group experiences. The boundary of such a specialist service however is unclear, and definition is difficult, given the varying experiences of the multiple stakeholder groups. Objectives: The study reported here quantitatively investigates divergence in stakeholders' views of what constitutes a good specialist service for people with intellectual disabilities. It is the first step of a larger project that aims to investigate the purpose, function and design of such a specialist service. The results are intended to support policy and service development. Study design: A Delphi study was carried out to elicit the requirements of this new specialist service from stakeholder groups. It consisted of three panels (carers, frontline health professionals, researchers and policymakers) and had three rounds. The quantification of stakeholder participation covers the number of unique ideas per panel, the value of these ideas as determined by the other panels and the level of agreement within and between panels. Findings: There is some overlap of ideas about of what should constitute this specialist service, but both carers and frontline health professionals contributed unique ideas. Many of these were valued by the researchers and policymakers. Interestingly, carers generated more ideas regarding how to deliver services than what services to deliver. Regarding whether ideas are considered appropriate, the variation both within and between groups is small. On the other hand, the feasibility of solutions is much more contested, with large variations among carers. Conclusions: This study provides a quantified representation of the diversity of ideas among stakeholder groups regarding where the boundary of a specialist service for adults with learning disabilities should sit. The results can be used as a starting point for the design process. The study also offers one way to measure the impact of participation for those interested in participation as a mechanism for service improvement.